2011
DOI: 10.1093/eurjhf/hfr047
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2, high-sensitivity troponin T- and N-terminal pro-B-type natriuretic peptide: complementary role for risk stratification in acutely decompensated heart failure

Abstract: AimTo investigate the use of biomarkers providing independent information regarding physiology in acutely decompensated heart failure (ADHF) for assessment of risk. Methods and resultsThis was a prospective study of 107 patients hospitalized with ADHF (mean age 72 + 13 years, 44% male, left ventricular ejection fraction 47 + 15%). Blood samples were collected on presentation to measure soluble (s)ST2, highsensitivity troponin T (hsTnT), and amino-terminal pro-B type natriuretic peptide (NT-proBNP) levels. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
147
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 35 publications
18
147
3
10
Order By: Relevance
“…A new and still not adequately investigated biomarker is soluble ST2, which is involved in cardiac remodelling and overload (54) . An increase in ST2 above 10 ng/mL is considered a predictor of mortality in patients with AHF (p < 0.001) (55) .…”
Section: Laboratory Biomarkersmentioning
confidence: 99%
“…A new and still not adequately investigated biomarker is soluble ST2, which is involved in cardiac remodelling and overload (54) . An increase in ST2 above 10 ng/mL is considered a predictor of mortality in patients with AHF (p < 0.001) (55) .…”
Section: Laboratory Biomarkersmentioning
confidence: 99%
“…In a brief communication, Mueller et al [6] reported that increased ST2 concentrations predicted 1-year mortality in 137 patients with acute destabilized HF. Later on, Pascual-Figal et al [7] demonstrated that ST2 provided prognostic value in addition to NT-proBNP and high-sensitivity troponin T in 107 patients with acutely decompensated HF. Recently, Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…ST2 is a protein of the interleukin-1 receptor family. Elevated serum levels of soluble ST2 are also associated with adverse outcomes in patients with acute decompensated or chronic HF [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hsTnT, NT-proBNP and sST2 offered complementary prognostic information in patients with ADHF, concluding that a panel containing these 3 biomarkers can provide superior risk stratification compared to the isolated use of each one. 27 Another prospective study on 202 patients with ADHF demonstrated that hsTnT assay offered an overall comparable prognostic information to conventional troponin T(cTnT). However, in unclear cases where cTnT was less precise or negative, increased levels of hsTnT were able to provide the requested prognostic information.…”
Section: C-reactive Proteinmentioning
confidence: 99%